Entrepreneurial competency training student's workbook - Diaz, Paz H.; Ching, Remedios S. ([Quezon City] EDCEL, PACSB, SERDEF, and UP-ISSI, 1993)
Contents: Unleashing personal potentials. Environmental scanning and opportunity identification. Project planning and feasibility study. It is a workbook for students engaging in the field of small and medium enterprise. It tackles small business management and entrepreneurial skills development. It is an output of the Entrepreneurial Development for the Collegiate Education Level (EDCEL) project that was implemented nationwide. It also includes modules for exercises.
Purpose: "It serves to stimulate the spirit of entrepreneurship among you and your classmates."
Keywords: Entrepreneurship -- Study and teaching -- Philippines -- Handbooks, manuals, etc; Small business -- Management -- Study and teaching -- Philippines -- Handbooks, manuals, etc; Competency based education -- Philippines -- Handbooks, manuals, etc